(3aQGFO GdahGFO hOQQ GdbdGFO hGdUdGI hGdYhGFOs - (3HOQ GdOjf eMeO Hf GdMSjf Hf SdjeGf GdeQgHj, CHj aGVds ((3eMeO Hf Ydi Hf eMeO Hf GdMSjf s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CXgQ ef YLGFH bOQJg , hGHQR ef HOGFY MceJg eG YLRJ Yfg CagGe GdYbhd (B[ (3hChd GdTYQ ef MQa GdgeRI eG jeOM Hg GdTQja YGed ecI GdeTQaI SYO Hf RjO fRdJ Ydi Mceg cja TGA CCMSf ai aYdg Ce CSeGA s
(3BNQgG (B:s
(3BNQg ef MQa GdjGA , ef bUjOI jNGWH HgG Gdabjg YeGO GdOjf jMji Hf Ydi GdOGFf heOGYHkG dg heG OMkG dg , Hbhdg (B: (3hSbjkG hQYjkG ddMeI hMdhdg hdhdGc ajg de Cbd ddMei SbjG Je GdOjhGf HMeO Gddg hefg s
(3HgG fXGe GdJYbjHIs
(3OjhGf TYQ eQJH Ydi MQha GdgLGAs
(3cJHJ HYV GdYfhGfGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs